ANALISIS KEKUATAN TEKAN BETON DENGAN AGGREGATE KASAR DARI BETON DAUR ULANG - Eri Setia Romadhon; Dwi Yulia Marthasari (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2021)
Concrete is the materials mixture between portland cement,water, soft aggregates, coarse aggregates with or without additif. Concrete is the materials mixture between portland cement,water, soft aggregates, coarse aggregates with or without additif. ¾ concrete composition is the aggregate, because the aggregate is very important things to make strength, minimum elasticity, water resistant concrete and reduce cement. Agregate recycling is the materials from old residue building. This research is trying to know about concrete strength from coarse aggregate recycling. Result from this research given that strength from concrete recycling and Concrete with aggregate split is the same.